2019
DOI: 10.15408/sjie.v8i2.10977
|View full text |Cite
|
Sign up to set email alerts
|

Islamic Bank Financing and Its Effects on Economic Growth: A Cross Province Analysis

Abstract: Islamic banking industry shows a reasonably good development, one of which is marked by an increase in service coverage in almost all provinces in Indonesia. However, the question is how far Islamic banking capable of contributing to the improvement of Indonesia's economic growth? The purpose of this research is to examine the role of Islamic banking in promoting inclusive economic growth with a sample of 33 provinces in Indonesia. The method used in this research is panel data regression using the fixed effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 13 publications
2
5
0
3
Order By: Relevance
“…Secara umum industri perbankan syariah di Indonesia telah menunjukkan perkembangan yang cukup baik, yang ditandai dengan adanya peningkatan layanan di hampir seluruh wilayah Indonesia (Afandi & Amin, 2019). Pada akhir tahun 2019, market share perbankan syariah Indonesia sebesar 5.95% dari keseluruhan market share perbankan nasional Indonesia.…”
Section: Pendahuluanunclassified
See 2 more Smart Citations
“…Secara umum industri perbankan syariah di Indonesia telah menunjukkan perkembangan yang cukup baik, yang ditandai dengan adanya peningkatan layanan di hampir seluruh wilayah Indonesia (Afandi & Amin, 2019). Pada akhir tahun 2019, market share perbankan syariah Indonesia sebesar 5.95% dari keseluruhan market share perbankan nasional Indonesia.…”
Section: Pendahuluanunclassified
“…Pembiayaan tersebut mencakup seluruh pembiayaan yang disalurkan (PYD) oleh perbankan syariah, namun belum diketahui pembiayaan mana yang memberikan kontribusi untuk pertumbuhan ekonomi baik jangka pendek maupun jangka panjang. Penelitian yang dilakukan oleh Afandi & Amin (2019) terkait pengaruh pembiayaan modal kerja, pembiayaan investasi dan pembiayaan konsumtif di 33 provinsi di Indonesia terhadap pertumbuhan ekonomi menunjukkan bahwa ketiga pembiayaan tersebut tidak berpengaruh terhadap pertumbuhan ekonomi Indonesia, sehingga keberadaan perbankan syariah di Indonesia belum memberikan dampak yang signifikan terhadap kesejahteraan masyarakat Indonesia. Pembiayaan modal kerja, pembiayaan investasi maupun pembiayaan konsumsi merupakan pembiayaan yang secara langsung berhubungan dengan aktivitas masyarakat.…”
Section: Pembiayaan Per Tahun (%)unclassified
See 1 more Smart Citation
“…The absence of influences between Islamic banking financing on economic growth was also revealed by (Afandi & Amin, 2019). In his research, he revealed that investment financing has a negative effect on economic growth.…”
Section: Source: Eviewsmentioning
confidence: 95%
“…Banking plays its role by issuing bank deposit obligations that contribute to broad monetary aggregates. The Islamic banking industry has proven to be a contributor to the calculation of Indonesia's national income (Afandi and Amin, 2019).…”
Section: Linkage Between Bank Credit Theory Economic Growth and Monet...mentioning
confidence: 99%